Identifikasi Bakteri Staphylococcus Aureus Pada Flush Toilet Di Kampus A Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur - Aathifah, Zerlina; Azahra, Sresta; Rica, Fitri Nur (Jurnal Kesehatan Lingkungan Mapaccing, 2024)
Sanitation facilities that have undergone many modifications are toilets. The occurrence of toilet modifications is influenced by the rapid growth of the population, causing limited sources of clean water. To anticipate these changes, the use of the toilet flush button can adjust the amount of water released in order to save clean water. The hand touching the surface of the toilet flush button plays an important role in the transmission of Staphylococcus aureus bacteria from one user to another. The purpose of this study was to determine the contamination of S.aureus bacteria on the toilet flush button in the campus A environment of the East Kalimantan Health Polytechnic. This research is descriptive. The sampling technique used is consecutive sampling. The sample calculation in this study used the slovin formula so that the number of samples was obtained as many as 18 pieces. A swab sample of the toilet flush button was taken at 16.00 WITA after the end of the academic community activities. The identification results of this study showed that from 18 toilet flush button swab samples there was S.aureus with a percentage of 78.8% and 22.2% there was no S.aureus. Due to the huge contamination by S.aureus on the toilet flush button, it is expected that toilet users to keep the toilet clean and wash their hands before and after using the toilet.